Characterization of systemic immunosuppression by IDH mutant glioma small extracellular vesicles. Issue 2 (13th July 2021) - Ludwig, Nils; Rao, Aparna; Sandlesh, Poorva; Yerneni, Saigopalakrishna S; Swain, Alexander D; Bullock, Kristin M; Hansen, Kim M; Zhang, Xiaoran; Jaman, Emade; Allen, Jordan; Krueger, Katharine; Hong, Chang-Sook; et al.
Abstract: Background: Gliomas are the most common primary brain tumors and are universally fatal. Mutations in the isocitrate dehydrogenase genes (IDH1 and IDH2) define a distinct glioma subtype associated with an immunosuppressive tumor microenvironment. Mechanisms underlying systemic immunosuppression in IDH mutant (mutIDH) gliomas are largely unknown. Here, we define genotype-specific local and systemic tumor immunomodulatory functions of tumor-derived glioma small extracellular vesicles (TEX). Methods: TEX produced by human and murine wildtype and mutant IDH glioma cells (wtIDH and mutIDH, respectively) were isolated by size exclusion chromatography (SEC). TEX morphology, size, quantity, molecular profiles and biodistribution were characterized. TEX were injected into naive and tumor-bearing mice, and the local and systemic immune microenvironment composition was characterized. Results: Using in vitro and in vivo glioma models, we show that mutIDH TEX are more numerous, possess distinct morphological features and are more immunosuppressive than wtIDH TEX. mutIDH TEX cargo mimics their parental cells, and induces systemic immune suppression in naive and tumor-bearing mice. TEX derived from mutIDH gliomas and injected into wtIDH tumor-bearing mice reduce tumor-infiltrating effector lymphocytes, dendritic cells and macrophages, and increase circulating monocytes. Astonishingly, mutIDH TEX injected into brain tumor-bearing syngeneic mice accelerate tumor growth and increase mortality compared with wtIDH TEX. Conclusions: Targeting of mutIDH TEX represents a novel therapeutic approach in gliomas.